The mitochondrial genome of Aenasius arizonensis (Hymenoptera: Encyrtidae) with novel gene order. Issue 1 (2nd January 2019) - Ma, Yue; Zheng, Bo-ying; Zhu, Jia-chen; Tang, Pu; Chen, Xue-xin
Abstract: Aenasius arizonensis is the endoparasitoid of mealybug ( Phenacoccus solenopsis ) and plays an important role in biological control. We sequenced the A. arizonensis mitochondrial genome using next-generation sequencing. The mitochondrial genome of A. arizonensis is 15, 373 bp in length with a typical 37 gene pattern. The base composition is AT-biased (79.61%). Both PCGs and tRNA gene rearrangement events are detected. Six PCG inversion events are detected in the mitochondrial genome of A. arizonensis. The tRNA gene shuffling between nad2 and nad3 was detected for the first time in Chalcidoidea mitochondrial genomes. The phylogenetic analysis supported the monophyly of Chalcidoidea. The sister group of (Trichogrammatidae + Encyrtidae) and Pteromalidae was corroborated by both Bayesian and maximum likelihood methods.